Movement Literation Educational Game Based On Dance Notation to Diagnostic Kinesthetic Intelligence of Junior High School Students - Devi Triana, Dinny; Panji Yudha, Rivo; Adhi, Bambang P (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
The purpose of this study is to be able to diagnose kinesthetic intelligence possessed by students with the help of educational games so that they have perceptual abilities through observing motion symbols that have an impact on body language. Besides that, it can optimize its creativity as humanistic literacy, by utilizing data available on the web as data literacy. The use of educational games is expected to make students feel happy and comfortable in participating in learning (joyful learning). Learning by using educational games will make students feel that the activity they are doing is playing games, but actually they are learning something that has been planned by the teacher. This research method uses Research and Development or R&D procedures. However, in this study only at the design stage of the motion literacy educational game prototype. Sampling used purposive with a total of 10 school teachers who have cultural arts teachers with a background in dance. Data analysis techniques to ensure that instruments in the form of motion literacy educational games become reliable devices through qualitative analysis with experts. This research produced a motion literacy educational game prototype consisting of instructions on how to play, manual, and start playing. This game can diagnose kinesthetic intelligence, critical and creative thinking skills in learning arts and culture in schools, especially dance, so that it can predict students' skills in dance.